Physiological and molecular response of Anadara tuberculosa (Arcoida: Arcidae) to salinity stress. - Mendoza, Oscar; Pretell, Krizia; Diringer, Benoit; Avellan, Ricardo; Zapata, Karina; Marchan, Angelita; Cedeño, Virna; Peralta, Tessy; Ordinola, Alberto; Mialhe, Eric (Revista de Biología Tropical, 2017)
The pustulose ark A. tuberculosa is an emblematic species of mangrove ecosystem that is currently in a vulnerable condition. The development of its aquaculture, to begin with genetic breeding programs, requires the identification of molecular biomarkers, particularly those associated with salinity stress. With this purpose, specimens of A. tuberculosa were collected from the adjacent mangroves of Puerto Pizarro bay (Tumbes, Perú), from January 2015 to February 2016. Different assays (groups of ten animals in triplicate) were undertaken in separated periods of 16 days: hypo-osmotic stress (extreme: 5, 10 ppt); (Moderate: 15, 25 ppt) and no stress (control group: 33 ppt). The presence of salinity stress biomarkers was assessed at the genetic level throughout PCR detection of 19 genes reported to be key actors in osmoregulation, and at the proteomic level with the sequencing of peptides (tandem mass spectrometry MALDI TOF/TOF), expressed in ark tissues exposed to different salinities. None of the tested genetic markers could be amplified by PCR, suggesting that A. tuberculosa has significant genetic differences compared to other mollusks. Proteomic analysis by mass spectrometry on A. tuberculosa gill tissue, allowed to identify 26 peptides expressed in presential and differential forms at different salinities, highlighting possible markers such as HSP70 and trans-membrane chloride channel transportation protein, to be related with salinity adaptation. These amino acid sequences will allow the design of target specific primers for A. tuberculosa, to implement future research in ecophysiology of this important fishery resource.